DESIGN AND IMPLEMENTATION OF SCADALARM IN A DRINK PRODUCTION PROCESS USING WONDERWARE - Sugiarto, Indar; Pasila, Felix (Institute of Research and Community Outreach, 2004)
Automation systems in industrial world need a kind of method to control automatically all continuing process from one to another. Besides, they also require monitoring process and remote controlling. For that reason they use SCADA which are using PLC(s) to implement such demand. One of the remarkable SCADA systems is Wonderware. This paper will describe a method of remote controlling and monitoring in SCADA system using Wonderware which is called SCADAlarm. We design a plant to simulate production process in a drink industry which is operated by PLC Omron C-200 HS and being connected by Intouch of Wonderware. SQL is used to acquire and store data and display them in the form of table or graphic. The simulation within InTouch and its real implementation on the plant gives the same result. The experiment shows that there is delay about 0.22 second up to 0.4 second for sending and receiving data. And for our simulation plant, the most appropriate modem is Rockwell 56 Kbps to implement SCADAlarm. The voice which are captured by the modem is clearly enough for communication. Abstract in Bahasa Indonesia : Dunia industri membutuhkan suatu sistem untuk mengontrol secara otomatis proses yang berkesinambungan dari proses yang satu ke proses yang lain. Selain itu juga dibutuhkan akan adanya proses monitoring dan pengontrolan jarak jauh. Untuk itulah digunakan SCADA Wonderware dengan menggunakan PLC. Makalah ini mencoba menjelaskan salah satu metode pengontrolan dan pemantauan jarak jauh dalam sistem SCADA menggunakan Wonderware yang disebut SCADAlarm. Metode tersebut diimplementasikan pada plant simulasi dari proses produksi minuman yang dioperasikan menggunakan PLC Omron C-200 HS dan dihubungkan dengan program Intouch pada Wonderware. SQL digunakan untuk mengambil dan menyimpan data dan ditampilkan dalam bentuk tabel/grafik. Simulasi di dalam InTouch dan implementasinya dalam plant memberikan hasil yang sama. Dari pengujian sistem terlihat adanya penundaan sebesar 0,22 detik hingga 0,4 detik untuk mengirim dan menerima data. Didapatkan juga bahwa modem yang digunakan yaitu Rockwell 56 Kbps sesuai untuk plant simulasi yang menggunakan SCADAlarm. Suara yang ditangkap dengan menggunakan modem ini cukup jelas untuk komunikasi. Kata kunci : SCADA intouch, SCADAlarm, database industrial SQL.